Konseling Pastoral: Upaya Pemulihan Batin Lansia Di Yayasan True Love Batam - Sanjaya, Yudhy; Siahaan, Renson; Kagu, Rosnita Temba; Kho, Yuvindro; Wasono, Wasono (Real Coster : Jurnal Pengabdian kepada Masyarakat, 2024)
Aging presents complex emotional challenges for elderly individuals (seniors). The elderly are at significant risk of prolonged emotional wounds caused by various factors such as social, emotional, and environmental influences, among others. This community service initiative aims to explore the role of pastoral counseling in healing the emotional wounds of seniors in nursing homes. The background emphasizes the need for attention to the psychological aspects of elderly well-being, given the negative impact of emotional wounds on their quality of life. The problem identification highlights key factors affecting the emotional well-being of the elderly, including the loss of a spouse, social isolation, and feelings of being unrecognized. The objective of the initiative is to apply a holistic and empathetic approach in pastoral counseling to help seniors overcome their emotional wounds. The evaluation of the process and outcomes of the healing efforts demonstrates the effectiveness of counseling interventions in creating positive changes in the emotional well-being of seniors. The results underscore the importance of greater attention to the psychological needs of the elderly and the role of pastoral counseling as an effective means of facilitating their emotional healing. Keywords: counseling; pastoral; inner recovery; elderlyAbstrakPenuaan membawa tantangan emosional yang kompleks bagi orang tua lanjut usia (lansia). Para Lansia mempunyai potensi yang besar terjadinya luka batin yang berlarut-larut oleh berbagai faktor seperti sosial, emosional, lingkungan dan lain sebagainya. Kegiatan pengabdian masyarakat ini bertujuan untuk mengeksplorasi peran konseling pastoral dalam memulihkan batin lansia di panti jompo. Latar belakang menggarisbawahi perlunya perhatian terhadap aspek psikologis dalam kesejahteraan lansia, mengingat dampak negatif luka batin terhadap kualitas hidup mereka. Identifikasi masalah mencakup kehilangan pasangan hidup, isolasi sosial, dan perasaan tidak diakui sebagai faktor utama yang memengaruhi kesejahteraan emosional lansia. Tujuan kegiatan adalah untuk menerapkan pendekatan holistik dan empatik dalam konseling pastoral untuk membantu lansia mengatasi luka batin mereka. Evaluasi proses dan hasil pemulihan menunjukkan efektivitas intervensi konseling dalam memberikan perubahan positif bagi kesejahteraan batin lansia. Hasilnya menegaskan pentingnya perhatian yang lebih besar terhadap kebutuhan psikologis lansia dan peran konseling pastoral sebagai sarana yang efektif dalam memfasilitasi pemulihan batin mereka.Kata Kunci: konseling; pastoral; pemulihan batin; lansia